(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
This study investigated the phytochemical composition of Phoenix dactylifera L. fruit, the effect of cadmium (Cd) on haematological parameters, and the potential of the methanolic extract of Phoenix dactylifera (MEPD) fruit to mitigate Cd-induced toxicity. Forty-five rabbit bucks (24–28 weeks old, 1.41–1.43 kg) were randomized into five groups: control, 3 mg CdCl₂/kg feed, Cd + 300 mg MEPD, Cd + 600 mg MEPD, and Cd + 900 mg MEPD. Cd was administered for 7 days, followed by MEPD treatment every 72 hours for 28 days. The result of phytochemical analysis showed the absence of tannins, phlobatannins, and starch, with a moderate presence of sterols and protein-xanthoproteins. Saponins, terpenoids, cardiac glycosides, alkaloids, phenols, and flavonoids were abundant. Haematological findings revealed no significant differences (P > 0.05) in the Cd-only group compared to the control. MEPD treatment produced a non-significant, dose-dependent increase in packed cell volume, haemoglobin, and red blood cell counts. Significant differences (P < 0.05) were found in mean corpuscular volume and mean corpuscular haemoglobin concentration, though all values remained within the normal range. Platelet counts, significantly (P < 0.05) reduced by Cd (204.30 ×10³/µl), improved significantly with MEPD treatment. This study highlights the phytochemical richness of Phoenix dactylifera and its potential to alleviate Cd-induced haematological toxicity.